2022
DOI: 10.3389/fbioe.2022.962114
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the therapeutic effect of unaltered versus NFκB sensing IL-4 over-expressing mesenchymal stromal cells in a murine model of chronic inflammatory bone loss

Abstract: Wear particles from joint arthroplasties induce chronic inflammation associated with prolonged upregulation of nuclear factor kappa-B (NF-κB) signaling in macrophages and osteoclasts, which leads to osteolysis and implant loosening. Mesenchymal stromal cell (MSC)-based therapy showed great potential for immunomodulation and mitigation of osteolysis in vivo, especially in the chronic phase of inflammation. We previously generated genetically modified MSCs that secrete the anti-inflammatory cytokine interleukin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…This treatment significantly reduces the number of OCs and effectively decreases local bone loss. 72 In a periodontitis model using diabetic rats, higher levels of macrophage infiltration and M1 macrophage polarization were observed compared to control groups. Additionally, when M1/M2 macrophages were treated with high levels of glucose, the supernatants increased the formation of OCs compared to cells cultured at normal glucose levels.…”
Section: The Role Of Macrophage Polarization In the Regulation Of Bon...mentioning
confidence: 98%
“…This treatment significantly reduces the number of OCs and effectively decreases local bone loss. 72 In a periodontitis model using diabetic rats, higher levels of macrophage infiltration and M1 macrophage polarization were observed compared to control groups. Additionally, when M1/M2 macrophages were treated with high levels of glucose, the supernatants increased the formation of OCs compared to cells cultured at normal glucose levels.…”
Section: The Role Of Macrophage Polarization In the Regulation Of Bon...mentioning
confidence: 98%
“…Blocking the secretion of the chemokine C-C-motif receptor (CCR1) in MSCs can lead to an increase in particles-induced osteolysis, suggesting that recruiting MSCs to inflamed areas helps limit inflammation and may contribute to bone regeneration ( Gibon et al., 2012 ). Recent studies have also shown that MSCs can increase the ratio of M2/M1 cells, reducing bone resorption and enhancing bone formation ( Shen et al., 2022 ; Kushioka et al., 2023 ). While MSCs primarily regulate adaptive immune responses in inflammatory diseases ( Bernardo and Fibbe, 2013 ), an increasing number of studies indicate their crucial role in modulating innate immunity ( Le Blanc and Mougiakakos, 2012 ).…”
Section: Cell-cell Interactionmentioning
confidence: 99%
“…It has been investigated that MSCs are activated and polarized in the inflammatory milieu of acute respiratory distress syndrome (ARDS) patients, shifting them toward a proinflammatory phenotype [16]. During bone regeneration or bone repair, the increase of pro-inflammatory cytokines such as IL-1, IL-4, IL-3, IL-6, IL-17a, IL-10, IL-22 and TNF-α leads to instability of the bone microenvironment, which affects the migration, repair, proliferation, and differentiation of MSCs [2,17]. Research evidence have shown that the adhesion and efficacy of MSCs in inflammatory arthritis can be regulated intraarticularly in mouse models, and inflammatory cells have anabolic effects on bone repair by recruiting MSCs and directing their migration and differentiation [18].…”
Section: Mscs and Inflammationmentioning
confidence: 99%